FLORISTIC AND STRUCTURAL CHARACTERIZATION OF THE MANGROVE FORESTS IN THE ESTUARY OF THE SÃO FRANCISCO RIVER - Santos, Tiago de Oliveira; Santana, Karen Viviane Andrade; Santos, Heide Vanessa Souza; Araújo Filho, Renisson Neponuceno; Holanda, Francisco Sandro Rodrigues (Floresta, 2019)
The objective of this work was characterize the floristic diversity and the phytosociological structure of the mangrove in the São Francisco River estuary in order to contribute to the conservation of this ecosystem. Thirty-four sampling sites were selected, according to ongoing structural mosaic in the region ranging from 100 to 400 m between themselves, in a total useful area of 0.7625 ha. The evaluated parameters were: density of live and dead trunks; living and dead Basal Area; Absolute Frequency, Relative Frequency and Importance Value. Three typical mangrove species of the São Francisco estuary were found such as Avicennia germinans (L.) Stearn, Rhizophora mangle L. and Laguncularia racemosa (L.) Gaertn. F. Gaertn. The forest height ranged from 2.88 to 15.63 m, the DBH from 3.95 to 19.74 cm, live basal area from 4.22 to 47.83 m² ha-1 and dead basal area from 0.50 to 59.63 m² ha-1. The living trunks density ranged from 375.00 to 9100.00 trunks ha-1 and dead trunk density from 100-2800 trunks ha-1. The described results in this study demonstrated that the mangrove forests presents a structural variability that may be associated with environmental characteristics (marine erosion) and anthropogenic factors. The peculiarities of each site emphasize the importance of preventive actions in the ecosystem conservation.